Addressing the specificities of contusion cataract surgery in adults - N.V. Kutukova; A. Yu. Kutukov; V.V. Brzheskiy (РМЖ "Клиническая офтальмология")
N.V. Kutukova1, A. Yu. Kutukov2, V.V. Brzheskiy2 1City Mariinskaya Hospital, St. Petersburg, Russian Federation 2St. Petersburg State Pediatric Medical University, St. Petersburg, Russian Federation Aim: to assess the clinical course and surgical procedures for contusion cataracts. Patients and Methods: 50 patients with a contusion cataract who underwent surgical treatment in 2008–2018 were included in the study group. 50 patients with a complicated cataract, either along with glaucoma (n=25) or diabetic cataract (n=25), were included in the control group. All patients were examined and treated in the same manner (i.e., eye exam was performed at admission, before the surgery, on postoperative days 1–3, and 1, 3, and 6 months after the surgery). Results: unilateral cataracts were revealed in the study group and bilateral cataracts were revealed in the control group. More than two-third of study group patients and only 14% of controls have the clinical signs of subluxated lens. In the study group, lens opacities were polymorphic. In the control group, nuclear opacities occurred in 30%, cortical opacities in 32%, and mixed opacities in 38%. In the course of  surgical procedures, previously undiagnosed mild lens subluxation was identified in 12% of study group patients and less than 6% of controls. The total rate of zonular insufficiency in the study group was twice as much as in the control group. Additional devices (i.e., iris and capsular retractors, capsular tension rings etc.) were used in 46% of study group patients and 20% of control group patients. Visual acuity more than 12/20 was reported in 86% of study group patients and only 32% of control group patients. Conclusions: the clinical course and surgical performance of contusion cataracts should be considered when examining and operating these patients. Occult minimal lens subluxation is also important. Keywords: complicated cataract, traumatic cataract, contusion cataract, lens subluxation, iris capsular retractor, capsular tension ring, surgical specificities. For citation: Kutukova N.V., Kutukov A.Yu., Brzheskiy V.V. Addressing the specificities of contusion cataract surgery in adults. Russian Journal of Clinical Ophthalmology. 2020;20(4):187–190. DOI: 10.32364/2311-7729-2020-20-4-187-190.